The Impact of Exchange Rate on the Gross Domestic Product (GDP) in Iraq for the period (2004-2022) - Ogge Mohi*, Wijjdan; Siham Dawood , Samir (Journal of Economics and Administrative Sciences, 2024)
Purpose: Measuring the connection between the effect of the (EX) and GDP in Iraq.Theoretical Framework: The research addressed the impact of the exchange rate on Iraq's gross domestic product. The research problem revolves around the lack of an exchange rate policy that stimulates investment and production as a result of the economic challenges that Iraq is suffering from, especially since the exchange rate is linked to the trends of the general budget and imports, which led to the weakness of the impact of this monetary instrument on the economy. Therefore, the research raises the problem of whether the exchange rate used in Iraq impacts the gross domestic product.Design/Methodology/Approach: The research approach describes the topic to be investigated through scientific accreditation and depicts the results that have been adhered to. An inductive approach was adopted to explain the theoretical aspects of the research, verify the hypothesis, and achieve the desired objectives of the study. In addition, a modern econometric approach was used to demonstrate the effectuation of (EX) on the structure of imports and GDP. The program (EViews10) was used, and the data used extended between (2004-2022). Findings: The (EX) indirectly affects the GDP, especially when the dinar is devalued against the dollar, increasing production costs. This results in higher prices for locally produced goods compared to imported ones, and due to competition, local production declines, thereby reducing GDP.Research, Practical & Social Implications: We propose a future research agenda and highlight the analysis of the nature of the connection between the (EX) and GDP in Iraq.Originality/Value: The current study adds scientific value to previous studies through its results, especially since the results indicated that the rise in the exchange rate leads to an increase in demand for oil exports. What distinguishes the study is that it examines the relationship between the exchange rate and the domestic product in an oil country like Iraq that suffers from distortions in the local economy.